Biznesowy model sieci międzyorganizacyjnej - Niemczyk, Jerzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This article is an attempt to create a conception of describing and analyzing interorganizational networks from the perspective of business models. The article contains the analysis of franchising networks, networks of agents, outsourcing networks and holdings. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 63-70